Apply BMWP Score System to Assess Water Quality of Some Runnning Water - Ha, Le Thu; Quynh, Nguyen Xuan; Yen, Mai Dinh (VNU Journal of Science: Natural Sciences and Technology; Vol 18 No 1, 2002)
Abstract